Addressing the spread of health-related misinformation on social networks: an opinion article - Polyzou, Maria; Kiefer, David; Baraliakos, Xenofon; Sewerin, Philipp (Frontiers in Medicine, 2023)
Misinformation both in general and in the health sector is a serious social problem, which has taken on major proportions worldwide in the recent COVID-19 pandemic. This article deals with the spread of misinformation in a general context and specifically in the health sector. It presents a theoretical view of the problem and analyzes the spread of misinformation with a focus on the health sector and mainly rheumatology. Finally, conclusions from the previous analysis are formulated as well as suggestions for reducing the spread of misinformation and dealing with this problem in the health sector.